The last to vanish [compact disc, unabridged] : a novel - Miranda, Megan (Audioworks, Simon & Schuster Audio, 2022)
Ten years ago, Abigail Lovett fell into a job she loves, managing The Passage Inn, a cozy, upscale resort nestled in the North Carolina mountain town of Cutter's Pass. Cutter's Pass is best known for its outdoor offerings, rafting and hiking, with access to the Appalachian Trail by way of a gorgeous waterfall, and its mysterious history. A string of unsolved disappearances has haunted the town, and it is once again thrust into the spotlight when journalist Landon West, who was staying at the inn to investigate the story, disappears himself. Abby has sometimes felt like an outsider within the community, but she's come to view Cutter's Pass as her home. When Landon's brother Trey shows up looking for answers, Abby can't help but feel the town closing ranks. And she's still on the outside. When she finds incriminating evidence that may bring them closer to the truth, Abby soon discovers how little she knows about her coworkers, neighbors, and even those closest to her.